PENGATURAN HUKUM TERHADAP PEREMPUAN PELAKU TINDAK PIDANA PERKOSAAN - Lukman Hakim; Endang Prasetyawati; Otto Yudianto (Yayasan Akrab Pekanbaru, 2019)
Crime is a form of deviant behavior (crime) that is always there and is inherent in every form of society. One form of crime that occurs at this time is the act of decency or rape.